Libraries for Refugees: The case of Myanmar Refugees along Thailand Border - Miyake, Takafumi (Access: An International Journal of Nepal Library Association, 2023)
This article illustrates the roles of community library in the care and maintenance phase of refugee population with the case of Myanmar refugees fled to Thailand border since mid-1980s. The author argues that refugees’ access to library services needs to be ensured as well as provision of water and sanitation, food, shelter, and medical service since the library preserves cultural identity and self-esteem of refugee populations who experience traumatic incidents.